Characterisation of promising phase change materials for high temperature thermal energy storage. (August 2019) - Jacob, Rhys; Liu, Ming; Sun, Yanping; Belusko, Martin; Bruno, Frank
Highlights: A ternary chloride eutectic (Ba-K-Na-Cl) and binary carbonate eutectic (K-Na-CO3 ) have been studied as high temperature PCMs. Melting point and latent heat determined as 542 °C and 165 J/g, respectively for Ba-K-Na-Cl eutectic, while it is 707 °C and 133 J/g for the K-Na-CO3 eutectic. Thermal cycling around each PCMs melting point show that there is minimal change in melting point or latent heat due to cycling. Expected cost of the PCMs is US 0.28–0.51/kg. Abstract: In the current study two phase change materials have been initially characterised as potential high temperature phase change materials (PCM) for thermal energy storage. Thermophysical properties such as melting/freezing point, latent heat, and specific heat capacity were determined using differential scanning calorimetry (DSC). Results from the uncycled PCMs show a melting point of 541.98 ± 0.15 °C and a latent heat of 164.96 ± 3.83 J/g for the lower temperature PCM (BaCl2 -KCl-NaCl), and 706.92 ± 0.34 °C and 133.14 ± 3.55 J/g for the higher temperature PCM (K2 CO3 -Na2 CO3 ). This largely compares well with the melting points and latent heats provided in literature. Theoretical predictions of other properties such as solid and liquid density, liquid thermal conductivity, and viscosity were also estimated. Lastly, samples of the PCM were also cycled up to 200 times with the melting point and latent heat measured. From the cycling results, the melting point and latent heat of samples cycled 200 times show almost no change. The measured melting point and latent heat after 200 cycles was found to be 541.30 ± 0.16 °C and 161.64 ± 2.60 J/g, respectively, for the low temperature PCM. Similarly, the higher temperature PCM showed good cycling stability after 200 cycles with a melting point and latent heat of 704.62 ± 0.29 °C and 135.42 ± 3.59 J/g, respectively. Overall, it was found that the PCMs investigated in the current study show promising results to be considered as high temperature energy storage materials.